PENINGKATAN KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBUATAN MODUL AJAR MELALUI BIMBINGAN DAN LATIHAN DI KECAMATAN BANDAR KABUPATEN BATANG - Sugito Sugito (CV. ADIBA AISHA AMIRA, 2023)
The competence becomes a purpose that must be achieved by a teacher based on standardization for developing profession ability so it gets on professional level. Being professional teacher must increase the competence in teacher. Therefore this research aims to describe it (pedagogic, personality, professional, and social ability) of religion teacher in This is field research using qualitative naturalistic method where researcher looks for and uses descriptive data such as words and opinion given by research subject. Data collection is conducted in interview and documentation method while analysis technique is conducted in data reduction, data presentation and conclusion. Data analysis is conducted while collecting data and after all data are collected or after the research is done in the field. This research shows that the effort that is done by religion teacher in Kecamatan Bandar Kabupaten Batang. in improving their competence is good but there is still something needed such as teacher personality training and the use of computer science and technology training.